Transcriptomic profiles of Clostridium ljungdahlii during lithotrophic growth with syngas or H2 and CO2 compared to organotrophic growth with fructose. Issue 1 (December 2017) - Aklujkar, Muktak; Leang, Ching; Shrestha, Pravin; Shrestha, Minita; Lovley, Derek
Abstract Clostridium ljungdahlii derives energy by lithotrophic and organotrophic acetogenesis.C .ljungdahlii was grown organotrophically with fructose and also lithotrophically, either with syngas - a gas mixture containing hydrogen (H2 ), carbon dioxide (CO2 ), and carbon monoxide (CO), or with H2 and CO2 . Gene expression was compared quantitatively by microarrays using RNA extracted from all three conditions. Gene expression with fructose and with H2 /CO2 was compared by RNA-Seq. Upregulated genes with both syngas and H2 /CO2 (compared to fructose) point to the urea cycle, uptake and degradation of peptides and amino acids, response to sulfur starvation, potentially NADPH-producing pathways involving(S) -malate and ornithine, quorum sensing, sporulation, and cell wall remodeling, suggesting a global and multicellular response to lithotrophic conditions. With syngas, the upregulated(R) -lactate dehydrogenase gene represents a route of electron transfer from ferredoxin to NAD. With H2 /CO2, flavodoxin and histidine biosynthesis genes were upregulated. Downregulated genes corresponded to an intracytoplasmic microcompartment for disposal of methylglyoxal, a toxic byproduct of glycolysis, as 1-propanol. Several cytoplasmic and membrane-associated redox-active protein genes were differentially regulated. The transcriptomic profiles ofC .ljungdahlii in lithotrophic and organotrophic growth modes indicate large-scale physiological and metabolic differences, observations that may guide biofuel and commodity chemical production with this species.